BATANG HARI REGENCY GOVERNMENT POLICY IN PRESERVINGLOCAL WISDOM FROM EXTINCTION - Ratna Dewi; Dori Efendi; Baidawi, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Prof Dr Hazairin, SH, 2023)
The purpose of this research is first, to see how the Batang Hari district government's policy is in preserving local wisdom from extinction, second, what local wisdom in Batang Hari district is almost extinct, and third, what is the role of the Malay traditional institutions of Batang Hari district towards preserving local wisdom. As we currently know, almost all countries are facing symptoms of an identity crisis and a cultural crisis. The method used in this research is descriptive qualitative research. Qualitative research is research used to examine the conditions of natural objects, where the researcher is the key instrument. The hypothesis of this research shows that the Batang Hari Regency government has a very big role in preserving local wisdom or regional culture from extinction through Malay traditional institutions and the Batang Hari Regency tourism and culture office.